Performance and characteristics of the Newborn Hearing Screening Programme in England: The first seven years - Wood, Sally A (Int J Audiol, 2015)
Objective: To assess the performance of the universal newborn hearing screen in England. Design: Retrospective analysis of population screening records. Study sample: A total of 4 645 823 children born 1 April 2004 to 31 March 2013. Results: 97.5% of the eligible population complete screening by 4/5 weeks of age and 98.9% complete screening by three months of age. The refer rate for the 12/13 birth cohort is 2.6%. The percentage of screen positive (i.e. referred) babies commencing follow up by four weeks of age and six months of age is 82.5% and 95.8% respectively. The yield of bilateral PCHL from the screen is around 1/1000. For bilateral PCHL in the 12/13 birth cohort the median age is nine days at screen completion, 30 days at entry into follow up, 49 days at confirmation, 50 days at referral to early intervention, and 82 days at hearing-aid fitting. Conclusion: The performance of the newborn hearing screening programme has improved continuously. The yield of bilateral PCHL from the screen is about 1/1000 as expected. The age of identification and management is well within the first six months of life, although there remains scope for further improvement with respect to timely entry into follow up.